2005
DOI: 10.1111/j.1365-4632.2005.02079.x
|View full text |Cite
|
Sign up to set email alerts
|

Bathing in a magnesium-rich Dead Sea salt solution improves skin barrier function, enhances skin hydration, and reduces inflammation in atopic dry skin

Abstract: Magnesium salts, the prevalent minerals in Dead Sea water, are known to exhibit favorable effects in inflammatory diseases. We examined the efficacy of bathing atopic subjects in a salt rich in magnesium chloride from deep layers of the Dead Sea (Mavena(R) Dermaline Mg(46) Dead Sea salt, Mavena AG, Belp, Switzerland). Volunteers with atopic dry skin submerged one forearm for 15 min in a bath solution containing 5% Dead Sea salt. The second arm was submerged in tap water as control. Before the study and at week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(70 citation statements)
references
References 31 publications
0
62
0
Order By: Relevance
“…The Chroma Meter Minolta ® is equipment employed to evaluate system of colors into three parameters: lightness (L*), proximity of red or green (a*), near the yellow or blue (b*) and situate the colors in these three coordinates [15]. Skin redness according to the methodology proposed by Proksch et al [16] will be analyzed indicates that inflammatory and anti-inflammatory action (increase and decreased of the parameter a*, respectively). After the formation of erythema, in the dorsal region of hairless mice, it will measure the color of the skin of animals, and later will be the application of the "test product" directly on the affected skin.…”
Section: In Vivo Study-evaluation Of Anti-inflammatory Activity Of Emmentioning
confidence: 99%
“…The Chroma Meter Minolta ® is equipment employed to evaluate system of colors into three parameters: lightness (L*), proximity of red or green (a*), near the yellow or blue (b*) and situate the colors in these three coordinates [15]. Skin redness according to the methodology proposed by Proksch et al [16] will be analyzed indicates that inflammatory and anti-inflammatory action (increase and decreased of the parameter a*, respectively). After the formation of erythema, in the dorsal region of hairless mice, it will measure the color of the skin of animals, and later will be the application of the "test product" directly on the affected skin.…”
Section: In Vivo Study-evaluation Of Anti-inflammatory Activity Of Emmentioning
confidence: 99%
“…Successful climatotherapy of atopic dermatitis requires strict medical supervision throughout the whole length of the patient's stay on shore. [23] The efficacy of DS bathing in atopic patients was studied by Proksch et al [10] The results demonstrate that bathing in the salt solution was well tolerated, improved the skin barrier function, enhanced the stratum corneum hydration and reduced the skin roughness and inflammation. The favorable effects of bathing in the DS are most likely related to the high magnesium content.…”
Section: Spa In Indiamentioning
confidence: 98%
“…Hence it is very useful in psoriatic patients who have a low magnesium level in the serum and scales. [10] Potassium is also a natural moisturizer. It is an astringent and antibacterial agent.…”
Section: Spa In Indiamentioning
confidence: 99%
“…Thus, salt from the Dead Sea is one of the most studied skin cosmetic ingredients due to its unique mineral composition. It was reported that Dead Sea-derived salt could be used to treat various skin conditions, inflammatory skin disorders and arthritis [2][3][4][5][6]. Also it improves skin barrier function and enhances skin hydration.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the benefits of the topical application of such minerals as magnesium and calcium was demonstrated in multiple balneotherapy studies, i.e. bathing in thermo-mineral waters or bath salts for home use [1,2].…”
Section: Introductionmentioning
confidence: 99%